2014
DOI: 10.1682/jrrd.2014.05.0118
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of microprocessor-controlled prosthetic knees to limited community ambulators: Systematic review

Abstract: The benefits of microprocessor-controlled prosthetic knees (MPKs) have been well established in community ambulators (Medicare Functional Classification Level [MFCL]-3) with a transfemoral amputation (TFA). A systematic review of the literature was performed to analyze whether limited community ambulators (MFCL-2) may also benefit from using an MPK in safety, performance-based function and mobility, and perceived function and satisfaction. We searched 10 scientific databases for clinical trials with MPKs and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 115 publications
(291 reference statements)
3
56
1
Order By: Relevance
“…[6,7] Access is often restricted to individuals with higher functional capability. This is in contrast to the findings of Kannenberg et al [8] and Wetz et al [9] who accentuated the overproportional benefits to individuals with more severe conditions and lower mobility grade ratings.…”
Section: Introductioncontrasting
confidence: 99%
“…[6,7] Access is often restricted to individuals with higher functional capability. This is in contrast to the findings of Kannenberg et al [8] and Wetz et al [9] who accentuated the overproportional benefits to individuals with more severe conditions and lower mobility grade ratings.…”
Section: Introductioncontrasting
confidence: 99%
“…Overall, the ICER was 16,132 Euro per QALY gained in amputees without DM and 20,332 Euro per QALY gained in amputees with DM. Several clinical and biomechanical studies [4][5][6][7][8][9][10][11][12][13][14][15] investigated the safety of the C-Leg compared to NMPKs. Results of these studies reported a reduction in falls and stumbles when patients used C-Legs instead of NMPKs.…”
Section: Discussionmentioning
confidence: 99%
“…The safe use of a prosthesis in activities of daily living is key for transfemoral amputees [4]. Several clinical and biomechanical studies as well as two systematic reviews [4][5][6][7][8][9][10][11][12][13][14][15] investigated the safety of using the microprocessor-controlled knee joint C-Leg (C-Leg). Compared with non-microprocessor-controlled (mechanical) knee joints (NMPK), the C-Leg reduced the number and frequency of stumbles and falls of up to 80% [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Elderly persons with TFA are thus at risk of denial of MPK consideration due to this requirement. However, limited community ambulators have been shown to gain as many (or more) of the benefits of MPK technology than their unlimited community ambulating peers (26). …”
Section: Discussionmentioning
confidence: 99%